Radiation-induced changes in dielectric and photoelectric properties of AᴵᴵBⱽᴵ crystals - Ryzhikov, V.; Starzhinskiy, N.; Chugai, O.; Seminozhenko, V.; Migal, V.; Komar, V.; Klimenko, I.; Katrunov, K.; Abashin, S.; Oleinik, S.; Sulima, S.; Zenya, I. (Functional Materials, 2004)
To determine the kinetics of pre-threshold defect formation, studies have been carried out of dielectric permittivity of isovalently doped zinc selenide and Cd₁₋ₓZnₓTe crystals (x = 0.16). X-ray irradiation of the samples was carried out (W-anode, 100-150 kV), with its dose D varied within the limits of up to 900 R. Dielectric parameters є' and є'' were measured by the capacitance technique in the frequency range 1...50 kHz. The photoactive states were studied by the method of scanning photodielectric spectroscopy. Non-trivial changes were noted in parameters є' and є'' upon increasing radiation dose. The values and sign of these changes depend upon the dose, as well as on frequency of the AC electric field. It has been shown that, starting from small values of D, transformation occurs of the system of intrinsic structure defects: concentration of initial defects is changed, new defects are formed, as well as their associates. Substantial difference has been noted in behavior of the said parameters for ZnSe and Cd₁₋ₓZnₓTe crystals. Для определения кинетики допорогового дефектообразования исследовалась диэлектрическая проницаемость изовалентно легированного селенида цинка и кристаллов Cd₁₋ₓZnₓTe (x = 0,16). Облучение образцов производили рентгеновским излучением (W-анод, 100-150 кВ), доза D которого варьировалась в пределах до 900 Р. Диэлектрические параметры є' и є'' измерялись емкостной методикой в диапазоне частот 1...50 кГц. Фотоактивные состояния исследовали методом сканирующей фотодиэлектрической спектроскопии. Обнаружены нетривиальные изменения параметров є' и є'' по мере возрастания дозы облучения. Величина и знак этих изменений зависят от дозы, а также частоты переменного электрического поля. Показано, что, начиная уже с малых значений D, происходит преобразование системы собственных дефектов структуры: изменяется концентрация исходных дефектов, образуются новые дефекты и их ассо-циаты. Наблюдаются существенные отличия в поведении указанных параметров для кристаллов ZnSe и Cd₁₋ₓZnₓTe. Для визначення кінєтики допорогового дефектоутворення досліджувалася діелектрична проникність ізовалентно легованого селеніду цинку та кристалів Cd₁₋ₓZnₓTe (x = 0,16). Опромінення зразків проводили рентгенівським випроміненням (W-анод, 100150 кВ), доза D якого змінювалась у межах до 900 Р. Діелектричні параметри є' та є'' вимірювалися ємосною методикою у діапазоні частот 1...50 кГц. Фотоактивні стани досдіджували методом скануючої фотодіелектричної спектроскопії. Знайдені нетривіальні змінення параметрів є' та є'' при зростанні дози опромінення. Величина і знак цих змінень залежать від дози, а також частоти змінного електричного поля. Показано, що, починаючи з малих значень D, відбувається перебудова системи власних дефектів структури: змінюється концентрація вихідних дефектів, утворюються нові дефекти та їхні асоціати. Спостерігаються суттєві відзнаки у поведінці вказаних параметрів для кристалів ZnSe та Cd₁₋ₓZnₓTe.